Intersektionalität und erzählte Welten – Einführung - Abrego, Verónica; Henke, Ina; Kißling, Magdalena; Lammer, Christina; Leuker, Maria-Th. (Intersektionalität und erzählte Welten. Fachwissenschaftliche und fachdidaktische Perspektiven auf Literatur und Medien)

Het verschil tussen strips en graphic novels (in Vlaanderen) - Lammer, Christina

Power-to-hydrogen and hydrogen-to-X energy systems for the industry of the future in Europe - Genovese, Matteo; Schlüter, Alexander; Scionti, Eugenio; Piraino, Francesco; Corigliano, Orlando; Fragiacomo, Petronilla (International Journal of Hydrogen Energy)
Keywords: Hydrogen economy; Green hydrogen; Power-to-X; Hydrogen-to-X; Sector coupling

Pre-equilibrium photons from the early stages of heavy-ion collisions - Oscar Garcia-Montero, Oscar Garcia-Montero; Mazeliauskas, Aleksas; Plaschke, Philip; Schlichting, Sören (arXiv:2308.09747)
We use QCD kinetic theory to compute photon production in the chemically equilibrating Quark-Gluon Plasma created in the early stages of high-energy heavy-ion collisions. We do a detailed comparison of pre-equilibrium photon rates to the thermal photon production. We show that the photon spectrum radiated from a hydrodynamic attractor evolution satisfies a simple scaling form in terms of the specific shear viscosity $η/s$ and entropy density $dS/dζ \sim {\scriptstyle \left(Tτ^{1/3}\right)^{3/2}}_∞$. We confirm the analytical predictions with numerical kinetic theory simulations. We use the extracted scaling function to compute the pre-equilibrium photon contribution in $\sqrt{s_{NN}}=2.76\,\text{TeV}$ 0-20% PbPb collisions. We demonstrate that our matching procedure allows for a smooth switching from pre-equilibrium kinetic to thermal hydrodynamic photon production. Finally, our publicly available implementation can be straightforwardly added to existing heavy ion models.

Open Educational Resources in der beruflichen Bildungslandschaft - Schneider, Jennifer Nicole

Experimental Study of an Internally Channeled Tube Heat Exchanger under Turbulent Flow Conditions - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny (International Journal of Heat and Mass Transfer)

A calibration method for failure modeling in clinching process simulations - Böhnke, Max; Bielak, Christian Roman; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)
Abstract. In the numerical simulation of mechanical joining technologies such as clinching, the material modeling of the joining parts is of major importance. This includes modeling the damage and failure behavior of the materials in accordance with varying occurring stress states. This paper presents a calibration method of three different fracture models. The calibration of the models is done by use of experimental data from a modified punch test, tensile test and bulge test in order to map the occurring stress states from clinching processes and to precisely model the resulting failure behavior. Experimental investigations were carried out for an aluminum alloy EN AW-6014 in temper T4 and compared with the simulative results generated in LS-DYNA. The comparison of force-displacement curves and failure initiation shows that the Hosford–Coulomb model predicts the failure behavior for the material used and the tests applied with the best accuracy.

Influence of plastic orthotropy on clinching of sheet metal - Friedlein, Johannes; Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)

Karneval und OWL - Breckner, Anne

Auszeit - Breckner, Anne

Was brauchst du? Engagement für die Mitmenschen in Christentum und Islam. Interreligiöse Unterrichtsreihe im Themenheft Diakonie - Breckner, Anne; Kamcili-Yildiz, Naciye (Religion 5-10)

Economic Integration of a High-Temperature Heat Pump with Flexible Part-load Operation - Knorr, Lukas; Schlosser, Florian; Meschede, Henning

Untersuchung des Reibungs- und Deformationsverhaltens von schnelllaufenden Bremsen - Rauhaus, Johann; Schadomsky, Magnus; Magyar, Balázs; Zimmer, Detmar (Tagungsband der 64. Tribologie-Fachtagung)

Übergang Schule-Beruf als Chancenverbesserungssystem – Zur Gestaltung von Lebensräumen und Entwicklung von Praktiken für den Übergang - Kremer, H.-Hugo; Otto, Franziska (bwp@ Berufs- und Wirtschaftspädagogik – online)
Sich wandelnde Bedingungen auf dem Ausbildungsmarkt, die daraus resultierenden veränderten Kompetenz- und Qualifikationsanforderungen sowie Anforderungen an eine lebensbegleitende berufliche Orientierung treffen insb. als (ausbildungs-)benachteiligt gekennzeichnete Jugendliche am Übergang Schule-Beruf. Jene Jugendliche münden in Maßnahmen des Übergangssystems wie die Ausbildungsvorbereitung (AV), wobei die konkreten Auswirkungen dieser Transformationsprozesse für diese Zielgruppe weitgehend unklar bleiben. In unserem Beitrag greifen wir die Überlegungen der Arbeitsgruppe 9+1 zum Übergangssystem verstanden als Chancenverbesserungssystem auf und diskutieren, was hierunter verstanden werden kann. Schließlich führen wir konkrete Anforderungen an das Chancenverbesserungssystem mit den Handlungsmöglichkeiten der Jugendlichen zusammen. Grundlegend verfolgen wir dabei nicht die Perspektive einer Anpassung der Jugendlichen an die Arbeitswelt, sondern fragen vielmehr danach, was Bildung leisten muss. Hierfür nehmen wir über qualitative Fallstudien die Perspektive der Jugendlichen sowie die Sichtweise des Bildungspersonals auf. In diesem Rahmen führen wir eine anforderungs- und subjektorientierte Perspektive zusammen und diskutieren u. a. anhand von Perspektiven auf das System, die curriculare Ebene, die Haltung der Bildungsakteur*innen, etc., was mit einer Gestaltung des Übergangssystems als Chancenverbesserungssystem konkret verbunden wäre.
Keywords: Übergangssystem; Selbstinszenierung; Chancenverbesserung; Subjektorientierung; Übergang Schule-Ausbildung

Selektives Lasersintern mit glasverstärkten Kunstsoff-Dry-Blends Analyse von Verarbeitbarketi und Bauteileigenschaften im Vergleich zu partikelgefüllten Kunststoffpulvern - Tschöpe, Jan-Cedric Philipp Balthasar

Investigating the Viability of Existing Exploratory Landscape Analysis Features for Mixed-Integer Problems - Prager, Raphael Patrick; Trautmann, Heike (Companion Proceedings of the Conference on Genetic and Evolutionary Computation, GECCO 2023, Companion Volume, Lisbon, Portugal, July 15-19, 2023)

A Bouquet of Encounters With Faux Flora Across Time – A Visual Essay. - Kraft, Kerstin

Influences on the Flow Behavior of Highly Viscous Thermal Interface Materials in the Joining Process - Gilich, Julian; Meschut, Gerson; Wiebicke, Felix; Gröger, Benjamin; Kuhtz, Moritz; Koch, Ilja; Gude, Maik (14th European Adhesion Conference (EURADH) & 7th World Congress on Adhesion and Related Phenomena (WCARP))

Innovation und neue Stabilitäten durch Krisenzeiten — zur Wandlungs- und Transformationsfähigkeit der beruflichen Integrationsförderung - Schemmer, Susanne Jutta (Arbeitsmarktgeförderte berufliche Integration, berufsbildung, 77 (3). Bielefeld: wbv Publikation, 2-4.)

Quo Vadis CO2 Activation: Catalytic Reduction of CO2 to Methanol Using Aluminum and Gallium/Carbon‐based Ambiphiles - Krämer, Felix; Paradies, Jan; Fernández, Israel; Breher, Frank (Chemistry – A European Journal)
Abstract We report on so‐called “hidden FLPs” (FLP: frustrated Lewis pair) consisting of a phosphorus ylide featuring a group 13 fragment in the ortho position of a phenyl ring scaffold to form five‐membered ring structures. Although the formation of the Lewis acid/base adducts was observed in the solid state, most of the title compounds readily react with carbon dioxide to provide stable insertion products. Strikingly, 0.3–3.0 mol% of the reported aluminum and gallium/carbon‐based ambiphiles catalyze the reduction of CO 2 to methanol with satisfactory high selectivity and yields using pinacol borane as stoichiometric reduction equivalent. Comprehensive computational studies provided valuable mechanistic insights and shed more light on activity differences.
Keywords: General Chemistry; Catalysis; Organic Chemistry